Large Farm Establishment, Smallholder Productivity, Labor Market Participation, and Resilience : Evidence from Ethiopia - Ali, Daniel; Deininger, Klaus; Harris, Anthony (World Bank, Washington, DC, 2016)
Although the nature and magnitude of (positive or negative) spillovers from large farm establishment are hotly debated, most evidence relies on case studies. Ethiopia’s large farms census together with 11 years of nation-wide smallholder surveys allows examination and quantification of spillovers using intertemporal changes in smallholders’ proximity and exposure to large farms, generally or growing the same crop, for identification. The results suggest positive spillovers on fertilizer and improved seed use, yields, and risk coping, but not local job creation, for some crops, most notably maize. Most spillovers are crop-specific and limited to large farms’ immediate vicinity. The implications for policy and research are drawn out.